Data collection with a tailored X‐ray beam size at 2.69 Å wavelength (4.6 keV): sulfur SAD phasing of Cdc23Nterm. Issue 3 (1st March 2016) - Cianci, Michele; Groves, Matthew R.; Barford, David; Schneider, Thomas R.
Abstract : Data collection with a tailored 50 µm diameter X‐ray beam at 4.6 keV (λ = 2.69 Å) on the newly established EMBL beamline P13 at PETRA III allowed the crystal structure determination of the Cdc23 Nterm homodimer (65.4 kDa; 12 Cys and ten Met residues) by sulfur SAD phasing at 3.1 Å resolution while overcoming crystal twinning. Abstract : The capability to reach wavelengths of up to 3.1 Å at the newly established EMBL P13 beamline at PETRA III, the new third‐generation synchrotron at DESY in Hamburg, provides the opportunity to explore very long wavelengths to harness the sulfur anomalous signal for phase determination. Data collection at λ = 2.69 Å (4.6 keV) allowed the crystal structure determination by sulfur SAD phasing of Cdc23 Nterm, a subunit of the multimeric anaphase‐promoting complex (APC/C). At this energy, Cdc23 Nterm has an expected Bijvoet ratio ⟨| F anom |⟩/⟨ F ⟩ of 2.2%, with 282 residues, including six cysteines and five methionine residues, and two molecules in the asymmetric unit (65.4 kDa; 12 Cys and ten Met residues). Selectively illuminating two separate portions of the same crystal with an X‐ray beam of 50 µm in diameter allowed crystal twinning to be overcome. The crystals diffracted to 3.1 Å resolution, with unit‐cell parameters a = b = 61.2, c = 151.5 Å, and belonged to space group P 43 . The refined structure to 3.1 Å resolution has an R factor of 18.7% and an R free of 25.9%. This paper reports the structure solution, related methods and a discussion of the instrumentation.